HUBUNGAN KONSENTRASI KLOROFIL-A DAN SUHU PERMUKAAN LAUT DENGAN HASIL TANGKAPAN IKAN PELAGIS UTAMA DI PERAIRAN LAUT JAWA DARI CITRA SATELIT MODIS - Ega Putra; Jonson Lumban Gaol; Vincentius P. Siregar (Jurnal Teknologi Perikanan dan Kelautan, 2012)
This research aims to study spatial and temporal variation of chlorophyll-a concentration and sea surface temperature as well as his relationship with pelagic fish catches in Java Sea. The results showed in 2006th-2010th sea surface temperaturerice occurs by 1°C which monthly average range between 27,9°C – 31,4°C. Sea surface temperature are relatively higher in transitional seasons compared to west season and east season. Chlorophyll-a concentration in area of research ranging from 0,22 mg/m³- 1,15 mg/m³. Chlorophyll-a concentration value each month fluctuates follow wind of progress. Maximum value of chlorophyll-a concentration happening in wesh season and minimum value occurs in transitional season 2. Layang scad, banyar fish and eastern little tuna has a negative response to sea surface temperature especially in east season. As for sardine fish and fringescalle sardine show absence of a direct relationshop between sea surface temperature with CPUE value catches. Sardine fish and fringescalle sardine show any positive response to rising chlorophyll-a concentration, while for layang scad, banyar fish and eastern little tuna an increase value of chlorophyll-a concentration does not have a direct impact on rising CPUE value of third type of this fish.